Pendampingan Pembuatan Video Pembelajaran Menggunakan Open Broadcast Software Bagi Guru - Firman Noor Hasan; Yos Nofendri; Muchammad Sholeh; Irfan Ricky Affandi (Universitas Lancang Kuning, 2022)
The government imposed LFH (Learning From Home) and WFH (Work From Home) during the PSBB implementation in each region due to the spread of the Covid-19 pandemic throughout the world. Educators, especially teachers, are required to organize online teaching and learning activities. The purpose of this activity is so that teachers no longer have difficulty in utilizing and using ICT technology, especially in making learning videos for subject matter, so that students or students can easily understand the material provided, thus indirectly motivating students in study. The form of implementation is carried out virtually accompanied by practical tutorials using the zoom meeting platform. The results of the evaluation questionnaire which were filled out by the activity participants after the service activities were completed, resulted in 52.23% who were satisfied while 44.06% of the participants felt strongly agreed and very satisfied & greatly helped by the service activities in the form of assistance in making learning videos using OBS software.